A Dendritic Cell Vaccine Combined With Radiotherapy Activates the Specific Immune Response in Patients With Esophageal Cancer. Issue 2 (February 2017) - Wang, Chengshi; Pu, Juan; Yu, Hanxu; Liu, Yanyan; Yan, Honghuan; He, Zhongxiang; Feng, Xin
Abstract : Dendritic cells (DC) are highly efficient antigen-presenting cells. DC may be used to create DC vaccines against cancer, but the optimal strategies remain to be elucidated. This study aimed to examine the benefits and adverse effects of using esophageal cancer cell antigens to stimulate DC to trigger the specific immune response in patients with esophageal cancer undergoing radiotherapy. This was an observational cohort study performed at Lianshui County People's Hospital between September 2010 and June 2012. Forty patients with esophageal cancer planned to receive radiotherapy were selected, and 28 received the DC vaccine. DC were isolated, loaded with antigens, and intradermally injected after being cultured for 1 week. One week after injection, the patients underwent a delayed-type hypersensitivity test. Serum Th1 cytokines [interleukin (IL)-2, IL-12, and interferon (IFN)-γ] and antigen-specific IFN-γ + CD8 + T cells were tested before and after vaccination. Patients were followed up for 2 years. Adverse events were monitored. Patients in the vaccine group tolerated the DC vaccine. Levels of serum IL-2 (+92.4%), IL-12 (+70.9%), and IFN-γ (+214.3%) as well as the proportion of IFN-γ + CD8 + T cells (3.0–16.4-fold) were significantly increased compared with baseline and the control group (all P <0.05). The 1- (82.1% vs. 50.0%, P =0.04) and 2-year survival (67.8% vs. 33.3%, P =0.04) was improved by vaccination. Only 2 patients showed mild fever. In conclusion, the DC vaccine triggered the specific immune response and induced the secretion of Th1 cytokines. The vaccine may lead to better survival, but this have to be confirmed. Adverse events were rare and mild.